2015
DOI: 10.1111/cen.12715
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of maternal serum Follistatin concentration in normal pregnancy and preeclampsia

Abstract: These analyses would permit the consideration that changes in FST levels during pregnancy contribute to the control of the Act A system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…82 Another interesting finding was the low levels of FS in EPE, in line with previous reports of lower levels in PE, and an increase with gestational age in uneventful pregnancies. 28,83 Through neutralization of the TGF-β superfamily members, FS participates in various processes like cell growth, development, and differentiation, 84 and members of the FS family are suggested involved in CVD pathophysiology outside pregnancy. 30 Biomarkers specifically dysregulated for EPE were ST2, CX3CL1, and MMP3 (all elevated) as well as MMP1 (lower).…”
Section: Discussionmentioning
confidence: 99%
“…82 Another interesting finding was the low levels of FS in EPE, in line with previous reports of lower levels in PE, and an increase with gestational age in uneventful pregnancies. 28,83 Through neutralization of the TGF-β superfamily members, FS participates in various processes like cell growth, development, and differentiation, 84 and members of the FS family are suggested involved in CVD pathophysiology outside pregnancy. 30 Biomarkers specifically dysregulated for EPE were ST2, CX3CL1, and MMP3 (all elevated) as well as MMP1 (lower).…”
Section: Discussionmentioning
confidence: 99%
“…This group of non-pregnant women was included because in previous studies it has been shown that during the menstrual cycle some hormonal factors change over this period. Therefore a reference level of this factor during the follicular and luteal phase should exist, to be compared to levels in pregnant women 63 64 .…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples were separated by centrifugation at 1000 g for 15 minutes and stored at −80 °C until assay. Serum triglycerides, total cholesterol, High Density Cholesterol (cHDL), Low Density Cholesterol (cLDL), Very Low Density Cholesterol (cVLDL), glucose and insulin were measured as previously described41. The Homeostasis Model Assessment-Insulin Resistance index (HOMA-IR) was calculated in all subjects as described by Matthews et al 42…”
Section: Methodsmentioning
confidence: 99%